Bioethics and the Human Goods : An Introduction to Natural Law Bioethics - Gómez-Lobo, Alfonso, 1940-2011; Keown, John (Book collections on Project MUSE., 2015)
In this concise and accessible introductory text, Gómez-Lobo and Keown introduce a "human goods" approach to bioethics as an alternative to the dominant principle-based method in the field (best illustrated by Beauchamp and Childress, Principles of Biomedical Ethics, OUP). Following Aristotle and the natural law tradition, the authors demonstrate how an emphasis on human goods--such as health, life, family, friendship, work and play, the experience of beauty, knowledge, and integrity--provides a necessary context for medical decisions and can help us understand critical issues at the beginning and end of life. The manuscript includes two parts: Foundations and Issues. In the Foundations section the authors explain how one can think about bioethics, offering definitions of ethics and ontology (the study of being) and prudential reasoning. In the Issues section they address genetics, abortion, infanticide, suicide and physician-assisted suicide, nutrition and hydration, and transplantation ethics. The book includes appendices featuring personal statements by Gómez-Lobo on the status of the human embryo and criteria for the determination of death.